2011
DOI: 10.1590/s0004-282x2011000200002
|View full text |Cite
|
Sign up to set email alerts
|

CYP2C9 polymorphism in patients with epilepsy: genotypic frequency analyzes andphenytoin adverse reactions correlation

Abstract: Objective: CYP2C9 is a major enzyme in human drug metabolism and the polymorphism observed in the corresponding gene may affect therapeutic outcome during treatment. The distribution of variant CYP2C9 alleles and prevalence of phenytoin adverse reactions were hereby investigated in a population of patients diagnosed with epilepsy. Method: Allele-specific PCR analysis was carried out in order to determine frequencies of the two most common variant alleles, CYP2C9*2 and CYP2C9*3 in genomic DNA isolated from 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…Specifically, carriers of the variant CYP2C9*3 tended to require significantly lower maintenance phenytoin dosages (p < 0.0001) and generated significantly higher concentration-dose ratios than wild-type carriers (p < 0.004) [139]. This was not, however, confirmed in a separate study [140].…”
Section: Interactome Modelmentioning
confidence: 79%
“…Specifically, carriers of the variant CYP2C9*3 tended to require significantly lower maintenance phenytoin dosages (p < 0.0001) and generated significantly higher concentration-dose ratios than wild-type carriers (p < 0.004) [139]. This was not, however, confirmed in a separate study [140].…”
Section: Interactome Modelmentioning
confidence: 79%
“…Figure shows a flowchart of our search results. After filtering PubMed entries and publications from REFARGEN members, 72 articles were selected, 22 of which examined both pharmacogene(s) and drug(s) from a CPIC guideline (Table ). The remaining 50 articles investigated one or more genes comprised in the guidelines.…”
Section: Resultsmentioning
confidence: 99%
“…One study examined the impact of CYP2C9*2 and *3 genotypes on phenytoin adverse reactions and failed to detect an association, possibly because of the small size of the study cohort and the fact that most patients were receiving co‐medications . In a small subset of the same cohort, the authors observed a significant reduction in cerebellar white matter volume in carriers of CYP2C9 variants compared to wild‐type patients .…”
Section: Resultsmentioning
confidence: 99%
“…An early report of the group described no association of the studied polymorphisms ( with phenytoin dosage or ADRs [52], however the authors performed a further study with the same study group using imaging data to assess cerebellar atrophy signs and showed a reduction in cerebellar volume related to *2/*3 allele carriers [53].…”
Section: Cyp2c9mentioning
confidence: 95%